Watt-level sub-100 fs third near-infrared window laser generated by self-seeded coherent Raman amplification based on erbium-ytterbium co-doped fiber - Jiaxuan Zhang; Jintao Fan; Minglie Hu (High Power Laser Science and Engineering)
In this paper, we prove that the third near-infrared (NIR-III) window high-power laser with wavelength in the range of 1600–1800 nm can be obtained by the coherent Raman fiber amplification technique through theoretical and experimental study. Detailed numerical simulation reveals that the nonlinear dynamics of the Raman fiber amplification in the polarization-maintaining double-clad erbium-ytterbium co-doped fiber is similar to that of the Mamyshev oscillator. Through the spectral filtering effect induced by finite Raman gain, we can obtain a high-quality Raman pulse. According to the theoretical results, we design a simple Raman fiber amplification laser and finally obtain a high-quality watt-level NIR-III window laser pulse in which the central wavelength is about 1650 nm and the pulse width can reach 85 fs. The experimental results correspond to the simulation results. Such nonlinear effect is universal in all kinds of fibers, and we think this technology can provide a great contribution to the development of ultrafast fiber lasers.